SmartDelta: Automated Quality Assurance and Optimization in Incremental Industrial Software Systems Development - Saadatmand, Mehrdad; Enoiu, Eduard Paul; Schlingloff, Holger; Felderer, Michael; Afzal, Wasif (Proceedings (Euromicro Conference on Digital Systems Design), 2022)
A common phenomenon in software development is that as a system is being built and incremented with new features, certain quality aspects of the system begin to deteriorate. Therefore, it is important to be able to accurately analyze and determine the quality implications of each change and increment to a system. To address this topic, the multinational SmartDelta project develops automated solutions for quality assessment of product deltas in a continuous engineering environment. The project will provide smart analytics from development artifacts and system executions, offering insights into quality degradation or improvements across different product versions, and providing recommendations for next builds.